Effect of Expressive Arts Therapy Interventions on Comfort of Children Undergoing Surgery - Zeinab F. El Sayed; Bothayna N. Sadek (Evidence-Based Nursing Research)
Context: Children undergoing surgery may experience pain and discomfort. Unfortunately, it is not always possible to completely prevent postoperative pain and discomfort with analgesics. Therefore, there is an increasing interest in non-pharmacological interventions through expressive arts therapy.